Diversity, distribution and substrate specificity of fouling molluscs in the cochin backwaters - Aleena, K. (KUFOS, 2019)
Biofouling is defined as the attachment and subsequent growth of a community of visible plants and animals on structures and vessels exposed to water. Biofouling is one of the deterioration processes that affect all stationary and moving engineered structures irrespective of the nature and type of material employed. Biofouling comprises several benthic life forms, which attach themselves to the various artificial substrate. This study was carried out to analyze the diversity of fouling molluscs in the Cochin back waters, about the seasonal distribution of fouling molluscs in different regions of Cochin back waters and to investigate the physicochemical factors facilitating fouling with emphasis to their substrate specificity. A checklist of different groups of fouling organisms was prepared by compiling different works done in Cochin back waters out of which the present study concentrated only for fouling molluscs, which included bivalves and gastropods. Influence of environmental parameters to enhances the species diversity was also checked according to three seasons. For this study five different stations was selected and keep regular monthly interval of sampling. Physically and biologically inert substrates are more favourable for succession as well as abundance of fouling organisms. This present study provides bench mark data on the fouling molluscs diversity of Cochin back water.